Bioethical problems of medical education in the era of artificial intelligence - Chamba Cuadros, José (2024)
The discipline of bioethics has gained increasing importance in the field of medicine, serving as an essential framework for identifying and addressing emerging ethical conflicts. The objective of the present study is to analyze the bioethical challenges for medical training in the era of artificial intelligence (AI), with the purpose of stimulating critical reflection on the ethical implications of its use. A bibliographic review was carried out, using the following databases as sources of information: Dialnet, Pubmed, and Google Scholar. The exploration was carried out in a time interval of 2001-2023. In a first search, a total of 50 publications were collected, of which 23 bibliographic sources were selected, based on inclusion and exclusion criteria. It has been proven that artificial intelligence (AI) has experienced accelerated evolution, bringing with it a significant increase in the ethical challenges faced by medical personnel. These professionals find themselves having to navigate between commitment to the well-being of their patients and adaptation to new care modalities, such as telemedicine and virtual consultation. The importance of rigorous ethical reflection in the integration of these technologies in clinical practice is highlighted.